Capitalism and modern social theory an analysis of the writings of Marx, Durkheim and Max Weber - Giddens, Anthony (Cambridge, [England] Cambridge University Press, 1971)
This book offers a new analysis of the works of the three authors who have contributed most to establishing the basic framework of contemporary sociology. Recent scholarship has illuminated important aspects of the ideas of Marx, Durkheim and Weber, but has also given rise to a variety of divergent interpretations of their writings. One of the main objectives of Capitalism and Modern Social Theory is to dispel some of the obscurities and misunderstandings which have resulted. The first three sections of the book, based on close textual examination of the original sources, contain separate treatments of each writer. Mr. Giddens is particularly concerned to demonstrate the internal coherence of their respective contributions to social theory. The concluding part of the book discusses the principal ways in which Marx's standpoint can be compared and contrasted with the other two authors, showing that some of the conventional views on this matter are misconceived.
Marx -- Marx's early writings -- Historical materialism -- The relations of production and class structure -- The theory of capitalist development -- Durkheim -- Durkheim's early works -- Durkheim's conception of sociological method -- Individualism, socialism, and the "occupational groups" -- Religion and moral discipline -- Max Weber -- Max Weber : Protestantism and capitalism -- Weber's methodological essays -- Fundamental concepts of sociology -- Rationalisation, the "world religions," and Western capitalism -- Capitalism, socialism and social theory -- Marx's influence -- Religion, ideology and society -- Social differentiation and the division of labour -- Postscript : Marx and modern sociology.
Includes bibliographical references (pages 248-254) and index.
Keywords: Marx, Karl -- 1818-1883.; Durkheim, Emile -- 1858-1917.; Weber, Max -- 1864-1920.; Capitalism